Important issues related to the law of corresponding states for the charge transport in molecular junctions with graphene electrodes - Bâldea, Ioan (Organic electronics, 2017)
A recent experimental study [Jia et al., Science 352, 1443 (2016)] succeeded to fabricate photoswitches with unprecedented performances using single-molecule junctions based on graphene electrodes and diarylethene that switches between closed and open conformations. The current-voltage measurements reported in that study revealed the applicability of the recently deduced law of corresponding states for the transport by tunneling [Bâldea et al., Nanoscale 7, 10465 (2015)] in a certain range of biases. In the present paper, we demonstrate that the size of that bias range is motivated theoretically. Furthermore, by appropriately extending the theoretical framework, we find an improved agreement between the value of the HOMO energy offset relative to electrodes' Fermi level (which plays the role of a key parameter) extracted from transport data and the value obtained from microscopic calculations. Based on the shape of HOMO spatial distributions, we also present microscopic arguments on why the differences between the two aforementioned estimates for the two relevant (insulating, open and conducting, closed) molecular conformations are different. From a more general perspective, the analysis presented in this study provides important support in favor of a transport mechanism via tunneling in the molecular junctions studied by Jia et al.